Kształcenie kompetencji komunikacyjnej na lekcji języka obcego w kontekście współczesnych kontaktów językowych = Developing Communicative Competence During Foreign Language Lessons in the Context of Contemporary Language Contacts - Rapacka-Wojtala, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The educational process, regardless of its stage and level, should be adapted to the current communication circumstances. This is especially true about teaching and learning foreign languages, where the aim is to develop written and oral communication skills in everydaylife and professional situations.
Keywords: kompetencja komunikatywna; tekst; wypowiedź; typy kontaktów językowych; communicative competence; text; utterances; types of language contacts